Pelatihan Penyusunan Laporan Keuangan Berbasis Digital Pada Para Santri Pondok Pesantren Sirajussa’adah - Nurmatias Nurmatias; Nobelson Nobelson; Shinta Widyastuti; Alfida Aziz (IKRA-ITH ABDIMAS, 2023)
Regulation of the Minister of Home Affairs of the Republic of Indonesia No. 1 of 2013 that thegovernment supports efforts to realize the welfare of families and communities by empowering thecommunity. The variety of welfare-improving programs so far that are materially oriented has not hadmuch impact on reducing the poor This is due to the lack of consideration of the ecosystem aspects of anarea. So that the need for innovative efforts and knowledge to accelerate the alleviation of welfare inaddition to what has been done so far. Pondok Pesantren Sirajussa'adah, is one of the islamicboarding schools located in the village of Maruyung, Limo District, Depok, West Java, students asbusiness people with a micro scale are a form of responsibility in improving the economy,especially Pesatren Sirajus Sa'adah. Sirajussa'adah Islamic Boarding School has built islamic boardingschool business units that are handled and carried out by The main problem of this Pesantren is the lowquality of human resources (HR) caused by the lack of knowledge and understanding in recording eachtransaction and compiling financial reports. Therefore, activities are needed in community service aimedat students in the form of training with digital-based financial management. students in the form ofbusiness units which include the Tempe Industry, Pure Honey and Water RO Sirajussa'adah. which isquite easy and practical so that later it is expected to provide additional income for Pesatren SirajusSa'adah, so that with the empowerment of these students, it is also expected to be able to play a real rolein improving the economy of Pesatren Sirajus Sa'adah during the Covid-19 period. The approach methodis to provide training on Digital-based financial management applications so that it is hoped that businessactors in addition to increasing their income economically can also get additional financing from banks.